Optimation of Layers Thickness Design of Perovskite Solar Cell (PSC) Using GPVDM Simulation - Puspita, Dita (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2019)
In this research, perovskite solar cells by configuring ITO/PEDOT:PSS/CH3NH3PbI3/ZnO/Al changed to optimize their performance. Modifications are made by varying the thickness of each layer to increase the ideal thickness with an optimal power conversion efficiency (PCE) value. This research used GPVDM software to study several power conversion efficiency (PCE) parameters of ITO/PEDOT:PSS/CH3NH3PbI3/ZnO/Al solar cells. The results of the study show that the power conversion efficiency (PCE) can be increased by adjusting the thickness of the coating, in this study the ideal thickness with the highest power conversion efficiency 25.75% in 1x10-8 m of ITO, 1x10-6 m of PEDOT:PSS, 4x10-7 m of CH3NH3PbI3, 1x10-8 m of ZnO and 1x10-9 m of Al.